Konstruksi Sosial Kejahatan Siber: Analisis Teori Konstruktivisme Sosial Terhadap Proses Kriminalisasi dan Penanganan Kekerasan Berbasis Gender Online (KBGO) di Indonesia: Penelitian - Fadiel Sastranegara; Rosmalinda; Agusmidah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Online Gender-Based Violence is a form of cybercrime that has significantly increased in Indonesia and presents complex challenges for the national legal system. This issue is not only related to regulatory and law-enforcement aspects but also to social constructs influenced by cultural norms and patriarchal gender relations. In this context, a socio-legal study is needed to understand how social processes shape the meanings of “crime” and “victim” in OGBV cases and how these meanings affect criminalization and legal handling. This research aims to analyze the social construction of cybercrime, particularly OGBV, through the perspective of Berger and Luckmann’s social constructivism theory. The study employs a qualitative approach with a sociological-juridical method through legal document analysis and media discourse studies. The analysis examines how interactions among society, the media, and legal institutions influence the interpretation of perpetrators and victims within the context of gender-based digital violence. The findings show that the criminalization of OGBV perpetrators is not solely based on juridical aspects but is also a product of social constructions shaped by patriarchal values and gender bias. Responses to victims still face obstacles such as victim blaming and the low gender sensitivity of law-enforcement officers. In conclusion, law serves a dual function as both a product and an instrument of social construction. Therefore, gender-sensitive legal policies grounded in a constructivist perspective are needed to achieve substantive justice for OGBV victims.